2005
DOI: 10.1002/mus.20338
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle involvement in human immunodeficiency virus (HIV)–infected patients in the era of highly active antiretroviral therapy (HAART)

Abstract: Skeletal muscle involvement can occur at all stages of human immunodeficiency virus (HIV) infection, and may represent the first manifestation of the disease. Myopathies in HIV-infected patients are classified as follows: (1) HIV-associated myopathies and related conditions, including HIV polymyositis, inclusion-body myositis, nemaline myopathy, diffuse infiltrative lymphocytosis syndrome (DILS), HIV-wasting syndrome, vasculitic processes, myasthenic syndromes, and chronic fatigue; (2) muscle complications of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
61
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 134 publications
0
61
0
1
Order By: Relevance
“…The mechanism is multifactorial and likely comprises the effects of chronic viral infection, host response, anti-HIV medications, genetics, lifestyle/behavioral factors on intracellular signaling pathways, and substrate partitioning and sensing (9,10). Several groups have reported that HIV-associated insulin resistance is characterized by perturbations in glucose and lipid metabolism, which are common to type 2 diabetes (11)(12)(13)(14)(15)(16)(17)(18)(19). Whether HIV-associated insulin resistance is associated with defects in amino acid and protein metabolism has not been addressed.…”
mentioning
confidence: 99%
“…The mechanism is multifactorial and likely comprises the effects of chronic viral infection, host response, anti-HIV medications, genetics, lifestyle/behavioral factors on intracellular signaling pathways, and substrate partitioning and sensing (9,10). Several groups have reported that HIV-associated insulin resistance is characterized by perturbations in glucose and lipid metabolism, which are common to type 2 diabetes (11)(12)(13)(14)(15)(16)(17)(18)(19). Whether HIV-associated insulin resistance is associated with defects in amino acid and protein metabolism has not been addressed.…”
mentioning
confidence: 99%
“…A direct link between NRTI, mitochondrial dysfunction, and IBM is strongly suggested in a case of IBM in HIV infection 7 NRTI prolonged use may contribute to the development of IBM in this type of patients. In these cases the discontinuation of NRTI may be a strategy for management, although whether the condition is reversible remain unknown 7 .…”
Section: Discussionmentioning
confidence: 95%
“…Retroviral antigens have been detected in endomysial macrophages but not within the muscle fibers 6,7 . The activated CD8+ cells invade muscle fibres expressing MHC class I, as seen in retrovirus-negative polymyositis and IBM 6,11 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations